A Modified Endoscopic Access for Lumbar Foraminal Pathologies; Posterolateral “Intertransverse” Endoscopic Approach to Minimize Postoperative Dysesthesia Following Transforaminal Approach - Farah N. Musharbash; Sang Hun Lee (Neurospine, 2023)
Objective To present an innovative, modified endoscopic approach for foraminal/extraforaminal pathologies, to reduce postoperative dysesthesia (POD) following the conventional transforaminal endoscopic approach (the access angle more than 45° from the midline), since POD is one of the major documented disadvantages that may compromise patient satisfaction. Methods We introduce a modified posterolateral technique, termed the intertransverse approach, utilizing a steeper access angle less than 25° through the intertransversarii muscle and the intertransverse space with expanding Kambin triangle via lateral facetectomy/foraminoplasty, to reduce dorsal root ganglion/exiting nerve root irritation under direct visualization and lower the incidence of POD. Consecutive patients undergoing endoscopic spine surgery via the intertransverse approach for foraminal and/or extraforaminal disc herniations or bony stenosis were retrospectively reviewed. Clinical outcomes were reviewed with the primary outcome being POD. Results Twenty-two patients were included in the review. Patients showed significantly improved clinical outcomes (visual analogue scale leg and back pain and Oswestry Disability Index) postoperatively. There was a low rate of dorsal root ganglion (DRG)-related POD (9.1%, 2 of 22) that was minimal and resolved soon. Conclusion The inter-transverse endoscopic approach is feasible for lumbosacral foraminal and extraforaminal decompression with significantly improved clinical outcomes and the added advantage of a low rate of DRG-related POD compared to traditionally reported rates in the literature for the conventional transforaminal approach.